Childhood, migration and the pursuit of happiness in middle-class East Asia - Beck, F. (2024)
This special issue explores the shifting landscape of global middle-class migration within and from East Asia by taking the relationship between mobility, parenting ideals and changing educational desires as its focus. Contributions explore how East Asian middle-class families balance the emergent emphasis on their children's well-being with the demands of global competitiveness as these often-antagonistic desires are projected onto old and new migration destinations against the background of global geopolitical and economic power shifts. Instead of reifying the simplistic binary of hierarchical, achievement-oriented East Asian ‘Confucian educational norms’ versus democratic, well-being-focussed Western ideals, the contributions offer a nuanced understanding of how these educational ideals coexist within the social, cultural, political and economic contexts of families. By carefully assessing the dialectically entwined intimate experiences of parents and children, the articles collected here set out to broaden our understanding of how middle-class families in Singapore, South Korea, Japan and China attempt to negotiate the tension between prioritizing children's happiness and maintaining global competitiveness result in a variety of strategies from migrating to less obvious international destinations to crafting domestic alternatives. Taken together, the articles reveal consistent patterns of middle-class migration and child-rearing decisions that contest and reshape conventional notions of success, attesting to a shift in global middle-class migration trends and to the importance of child-rearing in migratory decisions.